CONTINUOUS MIDWIFERY CARE (CONTINUITY OF CARE) ON NY.L WITH MILD ANEMIA IN THE CLINIC PRATAMA NIAR, MEDAN AMPLAS KOTA DISTRICT MEDAN NORTH SUMATRA IN 2025 - Mestawati Zai; Ribur Sinaga; Juniarsih; Dermawi; Adzro Nabila; Mastaulina Srikana Pakpahan; Ade Riska Natalina Siringo Ringo, (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Anemia is characterized by a deficiency in circulating erythrocytes or hemoglobin levels, which compromises the blood's capacity to transport essential oxygen to bodily tissues. As outlined by Proverawati (2020), this clinical state is defined by gender-specific thresholds: hemoglobin concentrations falling below 13.5 g/dL in men and 12.0 g/dL in women. Furthermore, Varney (2019) specifies that for the pregnant population, a reading under 12.0 g/dL is indicative of anemia. It is estimated that iron deficiency serves as the primary etiology in these cases, accounting for nearly 95% of all gestational anemia occurrences.Anemia is characterized by a deficiency in circulating erythrocytes or hemoglobin levels, which compromises the blood's capacity to transport essential oxygen to bodily tissues. As outlined by Proverawati (2020), this clinical state is defined by gender-specific thresholds: hemoglobin concentrations falling below 13.5 g/dL in men and 12.0 g/dL in women. Furthermore, Varney (2019) specifies that for the pregnant population, a reading under 12.0 g/dL is indicative of anemia. It is estimated that iron deficiency serves as the primary etiology in these cases, accounting for nearly 95% of all gestational anemia occurrences.